Erosive wear characteristics of E‐glass fiber reinforced silica fume and zinc oxide‐filled epoxy resin composites. Issue 1 (20th August 2019) - Öztürk, Bülent; Gedikli, Hasan; Kılıçarslan, Yavuz S.
Abstract: In the present study, the effect of addition of silica fume, also known as microsilica, and zinc oxide fillers on the erosive wear behavior of bidirectional E‐glass fiber‐based epoxy resin composites has been investigated. The amount of silica fume and zinc oxide fillers in the composites was changed in the interval from 0 to 16 wt.%. The erosive wear of the composites has been evaluated at different impingement angles from 20° to 90° and at four different impact velocities of 70, 100, 150, and 200 m/s. The erodent particles used were silicon carbide (SiC) with the average particle sizes of 72 μm, 175 μm, and 348 μm, respectively. The results show that the erosion rate increases with increasing impingement angle, impact velocity, exposure time, and erodent particle size in all the composites. By comparing the two types of fillers, the composites filled with silica fume showed better erosion resistance than those of zinc oxide‐filled composites at the same filler loading. The composite filled with 16 wt.% silica fume presented the best erosion resistant while the highest erosion rate was obtained at the composite filled with 16 wt.% zinc oxide. The morphology of eroded surfaces was examined by using scanning electron microscopy, and possible erosion mechanisms were discussed.